THE EFFECTS OF EU R&I FUNDING ON SME INNOVATION AND BUSINESS PERFORMANCE IN NEW EU MEMBER STATES: FIRM-LEVEL EVIDENCE - Čučković, Nevenka; Vučković, Valentina (Economic Annals, 2021)
SMEs are the most dynamic and vibrant part of the enterprise sector in terms of start-ups and new jobs, and a sig-nificant share of the EU’s total innovation activities take place within them. This pa-per uses the Community Innovation Survey (CIS) 2014 and eCORDA data to analyse whether SME participation in EU research and innovation (R&I) funding programmes has increased their innovation activities and business performance. To achieve this, we empirically test whether SMEs that re-ceived EU funds recorded an improvement in their innovation and economic perfor-mance. This is measured by research and development (R&D) expenditure, product innovation, turnover, and employment. The paper focusses particularly on new EU member countries and among them to those from Central and Eastern Europe (CEE). It explores the theoretical and meth-odological backgrounds that guided us in these analyses and performs treatment ef-fect analysis at firm level, using CIS CD-ROM data that we received on request from Eurostat. The obtained results indicate that EU R&I funding is beneficial to the inno-vation activities of SME recipients, and to their overall business performance. It also assists new EU member states in the process of ‘catching up’ to the growth levels of more established EU economies.